Analisis Kebutuhan Petugas Unit Rekam Medis Berdasarkan Metode Workload Indicator Staff Need (WISN) di RSUD Wates Kulon Progo Yogyakarta - Aulia Alifariani; Nur Syarianingsih Syam (Universitas Ahmad Dahlan, 2021)
Medical record is a process that starts when a patient is received in health services, is forwarded to the data recording activities and continues to handle medical records which include the administration, storage and issuance of medical records from storage to serve loan requests for patient needs or in connection with legal requirements. the other. Planning for Human Resources for Health, Health Workers is every person who devotes himself in the field of health and has knowledge and or skills through education in the field of health which for certain types requires authority to make health efforts. WISN is an indicator that shows the amount of labor needs based on workload, so that the allocation of energy is easier and rational. The purpose of the study was to calculate the needs of medical record unit officers based on the Workload Indicator Staff Need Method (WISN) at Wates Kulon Progo District Hospital. This research uses descriptive qualitative method with a case study design. The technique of taking interview informants is using purposive sampling method with 4 informants. Subjects observed in this study were 9 medical records unit officers at the Wates Kulon Progo Regional District Hospital. Available working time at the medical records officer at Wates Kulon Progo Hospital in one year is 269 days or 2152 hours per year. The highest standard workload is based on a calculation of 129,120 minutes / year and the lowest is based on a calculation of 43,040 minutes / year. the allowance for medical records is 0.48. The number of medical records officers is 29 people. Based on WISN calculations, the number of workers in the Wates Kulon Progo Hospital Medical Record unit needs to experience additional staffing needs or can be optimized at any given point of work. One way to optimize labor through mutation of workers or optimization of labor can be done by rotation of workers.